Adolescent Resting State Networks and Their Associations with Schizotypal Trait Expression - Lagioia, Annalaura; Van De Ville, Dimitri; Debbané, Martin; Lazeyras, François; Eliez, Stephan (Frontiers in Systems Neuroscience, 2010)
The rising interest in temporally coherent brain networks during baseline adult cerebral activity finds convergent evidence for an identifiable set of resting state networks (RSNs). To date, little is know concerning the earlier developmental stages of functional connectivity in RSNs. This study’s main objective is to characterize the RSNs in a sample of adolescents. We further examine our data from a developmental psychopathology perspective of psychosis-proneness, by testing the hypothesis that early schizotypal symptoms are linked to disconnection in RSNs. In this perspective, this study examines the expression of adolescent schizotypal traits and their potential associations to dysfunctional RSNs. Thirty-nine adolescents aged between 12 and 20 years old underwent an eight minute fMRI “resting state” session. In order to explore schizotypal trait manifestations, the entire population was assessed by the Schizotypal Personality Questionnaire (SPQ). After conventional processing of the fMRI data, we applied group-level independent component analysis (ICA). Twenty ICA maps and associated time-courses were obtained, among which there were resting state networks (RSNs) that are consistent with findings in the literature. We applied a regression analysis at group level between the energy of RSN-associated time courses in different temporal frequency bins and the clinical measures (3 in total). Our results highlight the engagement of six relevant RSNs; 1) a default-mode network; 2) a dorso-lateral attention network; 3) a visual network; 4) an auditory network; 5) a sensory motor network; 6) a self-referential network. The regression analysis reveals a statistically significant correlation between the clinical measures and some of the RSNs, specifically the visual and the auditory network. In particular, a positive correlation is obtained for the visual network in the low frequency range (0.05 Hz) with SPQ measures, while the auditory network correlates negatively in the